Merdeka in West Papua: Peace, Justice and Political Independence - Webb-Gannon, Camellia (Anthropologica, 2014)
The vision for "Papua merdekaor a "peaceful, just and necessarily politically independent Papua" is perhaps the most powerful force of unity among West Papua's indigenous peoples. This article explores the origins of this supra-uniting vision and provides examples of how merdeka is envisaged by West Papuans as the best outcome of their struggle for peace with justice. It critiques the contested meanings of the term but demonstrates that there is considerable unity among West Papuan leaders regarding its components, and in the belief that merdeka cannot prevail in Papua without political inde pendence from Indonesia.